Approach of physical dysfunction in the initial training of physiotherapists/physiotherapists - Escobar-Cabello, Máximo (2020)
The essay identifies the structural factors of governmental power faced by people with physical dysfunction (PPD), integrating into the analysis the traditional training that kinesiologists / physiotherapists receive. The purpose of this approach is to show that the subsidies of the systemic structures are captured by a logic of reproduction that is born from the same world health organization (WHO), arriving to establish contradictorily before the complexity that this reality represents, a subsidiary conduct which holds the PPD responsible Faced with these events, a socio-critical approach is used to reveal that the structural constraints of power can only manage the insufficient existing subsidies. And that, in turn, this reality must be transformed into a prudent problematic nucleus to be incorporated into the formative processes of the curricular matrices of the physiotherapists who interact with property and frequently in these contexts. The document shows the socio-demographic scenario and the description of the status quo in order to interpret that with the theory of social reproduction or with the processes of official curricular innovation a sufficient burden is not achieved to modify reality, on the contrary, to assume that the transformation of the contexts can be built both from the reflection that induces the theory of resistance, and together with a critical position of training by competencies that does not elude sociohistorical commitment.